PENERAPAN SANKSI KODE ETIK TERHADAP ADVOKAT YANG MELAKUKAN PELANGGARAN PROFESI DI INDONESIA - Mardiana, Devi (Hukum dan Masyarakat Madani, 2022)
Indonesia as State Law based on Pancasila and the Constitution of the Republic of Indonesia Year 1945 guarantees equality for all before the law (equality before law). In realizing legal principles in society and stating, the role and function of Advocates as a profession that is free, independent and important is important, apart from judicial and law enforcement institutions such as the police and prosecutors. The purpose of writing this article is to examine how the implementation of code of ethics sanctions against lawyers who commit professional violations in Indonesia and what efforts can be made by lawyers who are sanctioned with violations of the code of ethics to raise objections. In carrying out their profession, Advocates are under the protection of the law, law and code of ethics. The legal profession code of ethics is the application of assigned duties that must be in accordance with the Integrated Criminal Justice System by demanding moral accountability to its clients, and to God (breaking the oath of office, abstaining from disgraceful acts, corruption)1and if the Advocate violates the provisions of the code of ethics then the case will be examined and tried by the Honorary Council. Keywords: Application; Code of Conduct Sanctions; Advocates.